Deciphering Phosphate Deficiency-Mediated Temporal Effects on Different Root Traits in Rice Grown in a Modified Hydroponic System - Negi, Manisha; Sanagala, Raghavendrarao; Rai, Vandna; Jain, Ajay (Frontiers in Plant Science, 2016)
Phosphate (Pi), an essential macronutrient for growth and development of plant, is often limiting in soils. Plants have evolved an array of adaptive strategies including modulation of root system architecture (RSA) for optimal acquisition of Pi. In rice, a major staple food, RSA is complex and comprises embryonically developed primary and seminal roots and post-embryonically developed adventitious and lateral roots. Earlier studies have used variant hydroponic systems for documenting the effects of Pi deficiency largely on primary root growth. Here, we report the temporal effects of Pi deficiency in rice genotype MI48 on 15 ontogenetically distinct root traits by using easy-to-assemble and economically viable modified hydroponic system. Effects of Pi deprivation became evident after 4 d- and 7 d-treatments on 2 and 8 different root traits, respectively. The effects of Pi deprivation for 7 d were also evident on 14 different root traits of rice genotype Nagina 22 (N22). There were genotypic differences in the responses of primary root growth along with lateral roots on it and the number and length of seminal and adventitious roots. Notably though, there were attenuating effects of Pi deficiency on the lateral roots on seminal and adventitious roots and total root length in both these genotypes. The study thus revealed both differential and comparable effects of Pi deficiency on different root traits in these genotypes. Pi deficiency also triggered reduction in Pi content and induction of several Pi starvation-responsive (PSR) genes in roots of MI48. Together, the analyses validated the fidelity of this modified hydroponic system for documenting Pi deficiency-mediated effects not only on different traits of RSA but also on physiological and molecular responses.